A Modern Poetics of Biography - Yang, Zhengrun. author. aut Link
XXXIX, 673 p. 2 illus.
Keywords: This book provides a comprehensive study of biography, to summarize the standard forms as well as a range of peripheral and expanded forms of auto/biography. Discussion and analyses to be done at three levels, namely ontology, typology, and writing. It is drawn from local and international theories in biography, in addition to related disciplines, in particular for those of the twentieth century, and summarizing the experiences of the writing of classics in both Chinese and Western biographical history, the study establishes a theoretical system of biography. This book can serve as a useful reference for postgraduate students and professional readers who are interested in biographical research.